Proceeding of the Third Asian Fisheries Forum, held at Singapore, 26-30 October 1992 - Proceeding of the Third Asian Fisheries Forum, held at Singapore, 26-30 October 1992 (The Asian Fisheries Society, 1994)
This is a superficial description of a much more complex situation. Fisheries worlwide, particularly in Asia, face a host of tough challenges in their collective efforts to steer the development of the fishery sector into the next decade. These challenges arise from four main areas: The increasing demand for fish; The extremely limited potential for increasing the fish supply from tradictional sources; Land, water and other resource constraints to increasing production from non-tradictional sources; Contraints to proper management of existing supplies